ЛИНГВОСТИЛИСТИЧЕСКИЕ ОСОБЕННОСТИ ПЕРВЫХ ТЮРКОЯЗЫЧНЫХ ПОЭМ (Eurasian Journal of Philology Science and Education, 2015)
The history of origin of literature written in Azerbaijani is looked through as compositional part of analogical events circulated throughout the world (in Europe and Russia). Creation of this history in Azerbaijan occurredafter the victory of Islam, in the result of local families joining in the same unique religious, later in the result of new rushing of Turkic people growing abruptly in 11th -13th centuries. Since 13th century Azerbaijani authorshad wrote their epic poems. The theme of the poems, like the ones in other countries throughout the world, was originated from the basic religious source the Koran, which plays the main role in the East. The poems about “Yusuf and Zuleykha”, based on the part about Yusuf prophet in the saint book, founded a capacious literature written in Azerbaijani. The initial ghazal patterns written under the influence of Arabian school of Aruz were included to these poems. The influence of literature of next time and their lingostylistic features in the article have being looked through.The works mentioned and the others, written under the influence of them, are found to reflect the passage to the classictime.